Indigenous fire stewardship shaped North American Great Lakes forests - Evan R. Larson; Nisogaabokwe Melonee Montano; Emily Lockling; Ashla Ojibway; Mocha B. Reynolds; Valerie Ross Zhaawendaagozikwe; Lane B. Johnson; Kurt F. Kipfmueller; Michael J. Dockry; Vern Northrup; Jeff Savage; Robin Wall Kimmerer (Proceedings of the National Academy of Sciences, 2025)
Interest in bringing Traditional Ecological Knowledge (TEK) and Western Science together to enhance climate and landscape resilience is growing rapidly, particularly for engagement with pyrogenic communities around the world. For these systems, Indigenous Knowledge offers unique insights that reflect millennia of intimate engagement with local landscapes, while Western Science can offer additional understanding of the emergence of climates and ecological conditions that are novel at evolutionary timescales. Here, we weave Indigenous Knowledge together with a multicentury history of fire, landuse, and forest development derived from tree rings to retell a more complete history of human engagement with the places commonly referred to as Wisconsin and Minnesota Points at the head of Lake Superior in the Laurentian Great Lakes. Our aim in this work is to create mutual reciprocal benefits for those involved in this work to disrupt a long history of extractive research and to honor the knowledge shared with us by reducing barriers to the revitalization of traditional cultural and landuse practices. This intensely local study, contextualized by substantial bodies of Indigenous Knowledge and Western Science, illustrates the importance of place-based and community-based research for understanding the role of Indigenous fire stewardship in shaping pine barrens sites and demonstrates how these fine-scale relationships are linked to regional landscape diversity yet may be invisible to other proxy-based studies. These results help (re)center Indigenous Knowledge and traditional fire-use practices in the process of ecocultural fire restoration for the creation of diverse, resilient, and just socioecological systems that continue to transition toward a warmer future.